PERBEDAAN HASIL BELAJAR STATIKA BERDASARKAN STRATEGI PEMBELAJARAN INKUIRI DAN KONVENSIONAL SISWA KELAS X PROGRAM KEAHLIAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 BUKITTINGGI - 366-373 , Ade Dwinta (Universitas Negeri Padang, 2014)
ABSTRACT This study aims to determine whether there is any effect of the application of inquiry learning strategies on student learning outcomes in subjects in class X statics Architecture Engineering SMK Negeri 1 Bukittinggi .This research is an experimental study , namely Pre - Experimental Designs. The population in this study were all students of class X in Architecture Engineering skills program at SMK Negeri 1 Bukittinggi school year 2013/2014. Based on the results of a comparative analysis on the obtained value of F test of homogeneity = 11.23 and F table = 2.05. These results show that the F value > F, meaning both groups of student learning outcomes data have variants that are not homogeneous. Furthermore, the test of homogeneity of variance obtained is not homogeneous and n1 ≠ n2 , then used t-tests with a separated variant . From the analysis of the data obtained and the price of t = 3.2 t table = 1.968 at 0.05 level. From these calculations it appears that t count > t table , this means that the hypothesis proposed in the study ( H0 ) is rejected. Keywords: Effects , Inquiry Learning Strategy , Learning Outcomes